Effect of Social Media Engagement and Beauty Influencers on Purchase Intentions of Indonesian Beauty Products - Basalamah, Rania Aysha Muhamad; Umayah, Anastasya; Wismiarsi, Tri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the relationship between social media engagement, influencers, and purchase intention for local beauty products in Indonesia. Apart from that, this research was also conducted to find out whether social media involvement mediates the relationship between influencers and purchase intentions. The research method used was a quantitative approach. The research sample includes Indonesian beauty product consumers who actively follow Indonesian beauty product influencers on social media. The data collection successfully recruits a total sample of 104 people, gathered using a purposive sampling technique. The research instrument used was adapted from previous studies and compiled into a questionnaire that was completed with five-point Likert scale answer choices. Based on the results of the analysis, beauty influencers do not directly impact purchase intentions but significantly increase social media engagement. Social media engagement, in turn, positively influences purchase intent and acts as a mediating variable between beauty influencers and purchase intention.